In vivo regeneration efficiency of enset (Ensete ventricosum (Welw.) Cheesman) as affected by age of parent plant and corm proportion - Fikadu Bora; Bewuketu Haile (CABI Agriculture and Bioscience)
Abstract In cultivation, E. ventricosum is propagated clonally with adventitious buds sprouting from callus formed on the cut surfaces of the corm. The present study was conducted to enhance the efficiency of this indigenous enset propagation technique by identifying the optimum age of parent plants and corm types for maximum shoot production. This study was conducted using corms in the range of 12–18, 20–28, 29–38, and 40–50 cm diameter, corresponding to four age classes (1, 2, 3 & 4 years old) and three corm treatments (whole, half and quarter) were arranged in 3 × 4 factorial combination and layout in randomized complete block design with three replications. The statistical program SAS Version 9.3 was used to examine the data. The result of the study showed that all of the parameters considered were significantly affected by the treatments or their interaction effects. The number of shoots produced per corm was significantly (p < 0.01) affected by the interaction of the age of the parent plant and corm treatment. The average number of shoots produced per corm was between 43 and 443 shoots per com. The highest shoot numbers (443 shoots per corm) were recorded on the 3-year plant using quarter corm; whereas the lowest number of shoots (43 shoots per corm) was obtained from whole corms of the 1-year plant. In general, the results of the study showed that the use of quartered corms of 3-year-old parent plants appears to be the efficient technique to regenerate enset in vivo.